Global existence and blow-up for a thermoelastic system with p-Laplacian. Issue 18 (12th December 2022) - Ding, Hang; Zhou, Jun
Abstract : In this paper, we study the following thermoelastic system with p -Laplacian 1 { u t t − Δ p u + θ = | u | r − 1 u, θ t − Δ θ = u t in a bounded domain Ω ⊂ R n, where u and θ denote the elongation of a plate and the temperature difference to the equilibrium state, respectively; Δ p denotes the classical p -Laplacian operator. By employing the potential well theory, we discuss the properties of global existence and finite time blow-up for the solutions. Moreover, we give the lower and upper bounds of blow-up time to the blow-up solutions.